Study of the amount of violence on four selected television programs - Clark, James (My University, 1977)
The purpose of this study was: (1) to determine the amount of violence on the television programs: Kojak, Starsky and Hutch, The Bugs Bunny Roadrunner Hour, and The All New Superfriends during the Fall of 1977; (2) to compare the amount of violence between the dramatic prime time presentations Kojak and Starsky and Hutch with the Saturday morning cartoon shows, The Bugs Bunny Roadrunner Hour and the All New Superfriends; and ( 3 ) to determine whether there is more violence on two prime time dramatic presentations or whether there is more violence on two children's Saturday morning cartoons. The selection of these programs was based on their longevity on the air, popularity with viewing audience, and recent events concerning one of the programs. The method used to determine the amount of violence in these programs was to tabulate each violent incident viewed on an individual program. Each violent incident was recorded on a monitoring instrument developed by the National Parent Teacher Association. The monitoring instrument divides violent incidents by categories. The results of this study indicate the the two children's Saturday morning cartoons reviewed are more violent than the two dramatic prime time programs reviewed. The Review of the Literature and Results of this Study have concluded that there is a great deal of violence in T.V. programming. More study is recommended to determine the effects of T.V. violence on the young viewer.
Keywords: Violence on television.; Television programs.